Three-dimensional discrete element modelling of rubble masonry structures from dense point clouds - Kassotakis, Nicko; Sarhosis, Vasilis; Riveiro, Belen; Conde, Borja; D'Altri, Antonio Maria; Mills, Jon; Milani, Gabriele; de Miranda, Stefano; Castellazzi, Giovanni (Automation in construction, 2020)
This paper presents a framework for the three-dimensional structural analysis of full scale, geometrically complex rubble masonry structures from point clouds generated from Structure-from-Motion photogrammetry or terrestrial laser scanning. According to the method, a point-based voxelization algorithm was adopted, whereby a dense point cloud was down-sampled into equidistant points, bypassing the need for conventional intensive processes, such as watertight mesh conversion, to obtain the geometric model of the rubble masonry for structural analysis. The geometry of the rubble masonry structure was represented by a sum of hexahedral rigid blocks (voxels). The proposed “point cloud to structural analysis” framework was implemented to assess the structural stability of the southwest leaning tower of Caerphilly Castle in Wales, UK. Simulations were performed with the three- dimensional computational software 3DEC, based on the Discrete Element Method (DEM) of analysis. Each voxel of the rubble masonry was represented as a rigid, distinct block while mortar joints were modelled as zero thickness interfaces which can open and close depending on the magnitude and direction of the stresses applied to them. The potential of the automated procedure herein proposed has been demonstrated to quantitatively assess the three-dimensional mechanical behaviour rubble masonry structures and provide valuable information to asset owners in relation to the structural health condition of assets in their care. •A procedure for DE modelling of rubble masonry from point clouds is proposed.•Rubble geometry represented by hexahedral rigid blocks bonded together.•The stability of the leaning tower of Caerphilly Castle evaluated.•The procedure presents a high degree of automation at each operational level.